2016
DOI: 10.1371/journal.pone.0165849
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Analysis of Preeclampsia Based on the Construction of an Extended Composite Network Featuring Protein-Protein Physical Interactions and Transcriptional Relationships

Abstract: Preeclampsia (PE) is a pregnancy disorder defined by hypertension and proteinuria. This disease remains a major cause of maternal and fetal morbidity and mortality. Defective placentation is generally described as being at the root of the disease. The characterization of the transcriptome signature of the preeclamptic placenta has allowed to identify differentially expressed genes (DEGs). However, we still lack a detailed knowledge on how these DEGs impact the function of the placenta. The tools of network bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
0
8
0
1
Order By: Relevance
“…It is unclear if the reduction in CLDN1 expression is causative or the result of repression due to increased levels of cytokines at the initiation of parturition. A recent meta-analysis of pre-eclampsia [ 46 ] demonstrated that CLDN1 was also downregulated suggesting a potential underlying mechanism to both idiopathic spontaneous and medically induced pre-eclampsia (PE) preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if the reduction in CLDN1 expression is causative or the result of repression due to increased levels of cytokines at the initiation of parturition. A recent meta-analysis of pre-eclampsia [ 46 ] demonstrated that CLDN1 was also downregulated suggesting a potential underlying mechanism to both idiopathic spontaneous and medically induced pre-eclampsia (PE) preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…A ausência de valores específicos do exame não impediu de verificar a associação com o desfecho, uma vez que não há relação entre a quantidade exata de proteína na urina, e, sim, sua ausência ou presença (17) . O ganho de peso e a obesidade foram significativos no 3º trimestre gestacional.…”
Section: Iresultadosunclassified
“…Meta-analysis of past studies enhances statistical power, which may highlight novel molecular pathways or strengthen the evidence for previously identified genes. Indeed, multiple meta-analyses have been performed for pre-eclampsia ( Kleinrouweler et al , 2013 ; Moslehi et al , 2013 ; Vaiman et al , 2013 ; van Uitert et al , 2015 ; Vaiman and Miralles, 2016 ; Brew et al , 2016 ) and preterm birth ( Eidem et al , 2015 ; Paquette et al , 2018 ), as well as for investigating sexual dimorphism of the placenta ( Buckberry et al , 2014 ) and understanding trophoblast differentiation in the context of hydatidiform moles ( Desterke et al , 2018 ). Nevertheless, lack of data access can hamper the ability to perform powerful meta-analyses.…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%